Visual adaptations to sports vision enhancement training . A study of collegiate athletes at the US Air Force Academy - Zupan, M. F.; Arata, A. W.; Wile, A.; Parker, R. (Optometry - Journal of the American Optometric Association, 2006)
The individual who can process more visual information in a shorter period and make the proper response will have an advantage in competition. As athletes tap out their potential in other aspects of their performance, like speed, power or strength, what will they turn to next to increase their performance? The trend seems to be that they will turn to vision training. The results of this study indicate that if an individual performs vision training, then their visual systems will continue to improve with practice similar to other types of training